Animal welfare in feeding of dairy calves - Spinelli, Higor Borges de Oliveira Franco; Martoni, Nadine Rodrigues; Souza, Rita de Cássia Bastos de; Leal, Alessandra Alevato Leal; Mendonça, Juliana França Monteiro de; Campos, Mariana Magalhaes (Pubvet, 2024)
With growing interest in animal welfare in dairy farming, farms are improving their management practices to increase productivity. This study analyzed the feeding management of calves on dairy properties, emphasizing the welfare and health of young animals, to guide producers in adapting the physiological and behavioral needs of calves and, consequently, improving their productivity. For this study, the Scielo, Google Scholar and Pubmed databases. Feeding management is fundamental for the well-being of dairy calves, including colostrum, breastfeeding, weaning, feeding with concentrate, and access to water. Poor nutritional management can result in deficiencies, especially after weaning. Nutritional and environmental enrichment can improve calves’ diets. As a result, dietary management that follows the natural patterns of dairy calves has significantly improved their quality of life, reduced unwanted behaviors and promoted healthier development, leading to an increase in food consumption, reduced discomfort, and faster, healthier animal development, resulting in greater production.
Keywords: Breastfeeding; calf feeding; farm animal welfare; food transition